2002
DOI: 10.1021/la0255424
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Reversible Organogels via “Latent” Gelators. Aliphatic Amines with Carbon Dioxide and Their Ammonium Carbamates

Abstract: Rapid and isothermal (at room temperature) uptake of CO2 by solutions or, in some cases, organogels comprised of a primary or secondary aliphatic amine (1) and an organic liquid leads to in situ chemical transformation to the corresponding alkylammonium alkylcarbamate (2) based gels. Chemical reversibility is demonstrated by removal of CO2 from 2-based gels upon gentle heating in the presence of nitrogen. This is a general strategy for reversible self-assembly or disassembly of molecular aggregates relying on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(101 citation statements)
references
References 58 publications
6
94
0
Order By: Relevance
“…The formation of carbamate salt from BA and CO 2 was also reported by Chatterjee et al, who noted its importance for the high BA selectivity [29]. The carbamate salt is unstable and so the corresponding primary amine can easily be obtained by heating [40]. Compared to medium (a), this medium (d)…”
Section: Medium (D)supporting
confidence: 54%
“…The formation of carbamate salt from BA and CO 2 was also reported by Chatterjee et al, who noted its importance for the high BA selectivity [29]. The carbamate salt is unstable and so the corresponding primary amine can easily be obtained by heating [40]. Compared to medium (a), this medium (d)…”
Section: Medium (D)supporting
confidence: 54%
“…Recently, they are shown to form efficient gelators to various solvents. 26 For example, in our previous report, 27,28 we found that the formation of organogel is mainly driven by the interaction between alkylamines and ethylene glycol (solvent). The introduction of sodium oleate can alter the solubility of hexadecylamines in ethylene glycol leading to the morphology change from spheres to fibres, which is based on the nucleation-crystallization mechanism.…”
Section: -20mentioning
confidence: 86%
“…Higher T m , ΔH, and lower ΔS values suggested that the GG organogels were more stable than the MG organogels. [37,38] Addition of drug did not cause any significant variation in the thermal properties of both the types of organogels.…”
Section: Thermal Analysismentioning
confidence: 91%